Development of Digital Module on Kinematics Material Assisted by Artificial Intelligence Video Through MOOCs for Eleventh-Grade HIGH School Students - Utami, Cindi Nabila; Eko Risdianto; Purwanto, Andik (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study aims to develop and test the feasibility of a digital kinematics module for grade XI high school students equipped with Artificial Intelligent (AI) videos and through the Massive Open Online Courses (MOOCs) platform. Analysis, Design, Development, Implementation, and Evaluation are the five steps of the ADDIE development model, which are used in the Research and Development (R&D) process. According to the analysis, students have difficulty understanding physics ideas because there are not enough interesting and interactive learning resources available. The digital module created includes practice questions, quizzes, and videos that are available anywhere, anytime. The results of the study are that students responded well to the curriculum, showing a satisfaction score of 83%. The Artificial Intelligent AI module provides a more engaging and significant educational experience, which is consistent with the Merdeka Curriculum's emphasis on technology-integrated learning.